Is there any relation between arterial stiffness and insomnia? A challenging question - ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT; SAYAR, NURTEN (SPRINGER HEIDELBERG, 2022)
Purpose Insomnia is a common sleep disorder which has high comorbidity with a number of cardiovascular diseases (CVD). As a possible risk factor for the CVDs, arterial stiffness may be assessed non-invasively by pulse wave velocity (PWV) and augmentation index (AI). The aim of this study was to evaluate any relation between insomnia and arterial stiffness. Methods Patients with insomnia were included in the study after the exclusion of other sleep disorders by polysomnography. Sleep quality and the degree of insomnia symptoms were evaluated by the Pittsburgh sleep quality index (PSQI) and insomnia severity index (ISI), respectively. PWV and AI were assessed by Mobil-O-Graph arteriograph system. Results Consecutive patients with insomnia (n = 72, 56 women, mean age 55.8 +/- 9.1 years) were included. Patients were grouped as those with severe ISI scores (22-28) and those with mild to moderate ISI scores (8-21). Despite no significant difference in characteristics and clinical data, patients with severe ISI scores had significantly higher total PSQI scores and NREM-2 with significantly lower REM duration. They also had significantly higher systolic blood pressure, mean blood pressure, pulse pressure, PWV, and AI compared to patients with mild and moderate ISI scores. Correlation analysis revealed that PWV and AI were significantly correlated with the ISI score and PSQI score. Conclusion There is a close relation between arterial stiffness and insomnia suggesting a risk for CVD in patients with insomnia.
Keywords: Arterial stiffness; Insomnia; Sleep apnea; Pulse wave velocity; SHORT-SLEEP DURATION; PULSE-WAVE VELOCITY; ALL-CAUSE MORTALITY; CARDIOVASCULAR RISK; BLOOD-PRESSURE; TASK-FORCE; ATHEROSCLEROSIS; ASSOCIATION; METAANALYSIS; QUALITY